Bryconamericus turiuba, a new species from the upper Rio Paraná system (Ostariophysi: Characiformes) - Langeani, Francisco [UNESP]; De Lucena, Zilda Margarete S.; Pedrini, Juliane Lima; Tarelho-Pereira, Fabrício José [UNESP] (My University, 2005)
Bryconamericus turiuba, new species, is described from the upper Rio Paraná system in Brazil. It differs from all congeners in the following combination of characters: 15-20 branched anal-fin rays; four or five scales in a transverse series from the dorsal-fin origin to the lateral line; shallow body (depth 23.6-30.6% of SL); 37-43 perforated lateral line scales; first, third, and fifth or, more rarely, first and fourth outer premaxillary tricuspid teeth projecting anteriorly; two to five tricuspid to pentacuspid maxillary teeth; dentary with three or four tricuspid or pentacuspid large teeth, followed by five to seven smaller conical to tricuspid teeth; a conspicuous dark, vertically elongate humeral spot, extending to below the lateral line; a dark dorsal stripe extending from the supraoccipital spine to the caudal peduncle with a gap at the adipose-fin base; caudal-fin lobes without conspicuous markings, uniformly pigmented along rays; mature males lacking hooks on the pelvic- and anal-fin rays. The new species is compared with the Bryconamericus species described from the basins of the Rio Paraná, Rio Paraguay, Rio São Francisco, and coastal Brazilian rivers. © 2005 by the American Society of Ichthyologists and Herpetologists.
Keywords: fish; new species; taxonomy; Brazil; Parana River; South America; Western Hemisphere; World; Bryconamericus; Bryconamericus turiuba; Characiformes; Ostariophysi